2007
DOI: 10.1890/1051-0761(2007)017[0034:sfstpa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Forest Structure, Timber Production, and Socioeconomic Effects in a Multi-Owner Province

Abstract: Protecting biodiversity has become a major goal in managing coastal forests in the Pacific Northwest--an area in which human activities have had a significant influence on landscape change. A complex pattern of public and private forest ownership, combined with new regulations for each owner group, raises questions about how well and how efficiently these policies achieve their biodiversity goals. To develop a deeper understanding of the aggregate effect of forest policies, we simulated forest structures, timb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Our results thus suggest that generalizing forest management for forest owner categories can lead to considerable over-or underestimation of ecosystem service provision in forest resource projections when the diversity of management strategies between and within owner categories is not accounted for. In contrast to technical and environmental constraints affecting forest management, social constraints are rarely taken into account in projections of forest resource development and wood mobilization scenarios [68], even though it has been shown that social constraints could have an important impact on future wood supply and forest development [4,12,16,19]. When the results of forest impact analysis are used as the basis for decisionmaking regarding the long-term use of forests, as is the case in Sweden, it is important that all relevant constraints within forest management are considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results thus suggest that generalizing forest management for forest owner categories can lead to considerable over-or underestimation of ecosystem service provision in forest resource projections when the diversity of management strategies between and within owner categories is not accounted for. In contrast to technical and environmental constraints affecting forest management, social constraints are rarely taken into account in projections of forest resource development and wood mobilization scenarios [68], even though it has been shown that social constraints could have an important impact on future wood supply and forest development [4,12,16,19]. When the results of forest impact analysis are used as the basis for decisionmaking regarding the long-term use of forests, as is the case in Sweden, it is important that all relevant constraints within forest management are considered.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the Diverse scenario to subjective interpretation of the NIPF owner's management strategies from [19] was tested by changing the most influential parameters: rotation length, harvest level and proportion of set-aside, creating two alternatives for the Diverse scenario, one with more intensive management (Diverse_m) and one with less intensive management (Diverse_l) ( Table 7). The applied parameter changes were meant to span a considerable, but still plausible range of parameter settings [49].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Capturing these processes typically requires a spatially explicit landscape model (see below). However, gap models can be linked with landscape models (e.g., Johnson et al 2007), and a new class of individual tree models can operate at landscape scales (Seidl et al 2012).…”
Section: Strengths and Weaknesses Of Gap-replacement Modelsmentioning
confidence: 99%
“…Examples of aggregated models for land use and management include Hartter and Boston's [34] model of land conversion to agriculture based on the caloric needs of households and Brown et al 's [35] model of land use change in the Upper Midwest region of the United States. Such models, focusing on the ecological impacts of harvesting and land use conversion, often simulate land use decision-making as a probability of land use transition based on observed transition rates without incorporating the social mechanisms underlying these transition decisions (e.g., [35][36][37][38][39]). Consequently, while forest ecosystem characteristics are disaggregated within these models, ownership decision-making is still aggregated by owner class (e.g., public, industrial, smallholder) and therefore is relatively homogenous within class.…”
Section: Introductionmentioning
confidence: 99%